Red yeast rice improves lipid pattern, high-sensitivity C-reactive protein, and vascular remodeling parameters in moderately hypercholesterolemic Italian subjects - Cicero, Arrigo F.G.; Derosa, Giuseppe; Parini, Angelo; Maffioli, Pamela; D’Addato, Sergio; Reggi, Alessandra; Giovannini, Marina; Borghi, Claudio (Nutrition research (New York, N.Y.), 2013)
Despite a recent health claim by the European Agency on Food Safety, the effect of high doses of dietary monacolin supplements from red yeast rice on cholesterolemia has not been tested in Italian subjects. Our aim via a crossover, double-blind, placebo-controlled randomized clinical trial was to test if a short-term treatment with 10 mg monacolins could improve lipid pattern, high-sensitivity C-reactive protein (hs-CRP), and vascular remodeling biomarkers in a small cohort of Mediterranean subjects. Thus, 25 healthy, mildly hypercholesterolemic subjects were enrolled, and after 4 weeks of a stabilization diet, subjects were randomized to the sequence placebo-washout-monacolins or monacolins-washout-placebo, with each period being 4 weeks long. At each study step, a complete lipid pattern, safety parameters, hs-CRP, and matrix metalloproteinases 2 and 9 levels were measured. When compared to the placebo group, monacolins-treated patients experienced a more favorable percent change in total cholesterol (-12.45%, 95% CI −16.19 to −8.71), low-density lipoprotein cholesterol (−21.99%, 95% CI −26.63 to −17.36), non–high-density lipoprotein cholesterol (−14.67%, 95% CI −19.22 to −10.11), matrix metalloproteinase 2 (−28.05%, 95% CI −35.18 to −20.93), matrix metalloproteinase 9 (−27.19%, 95% CI −36.21 to −18.15), and hs-CRP (−23.77%, 95% CI −30.54 to −17.01). No significant differences were observed in regards to triglycerides, high-density lipoprotein cholesterol, and safety parameters. On the basis of our data, we demonstrate that a 10-mg monacolin nutraceutical appears to safely reduce cholesterolemia, hs-CRP, and markers of vascular remodeling in Italian subjects. These results have to be confirmed in larger patient samples and longer studies.